Q Methodology: An interesting strategy for concept profile and sensory description of low sodium salted meat. (March 2020) - Vidal, Vitor A.S.; Paglarini, Camila S.; Freitas, Mônica Q.; Coimbra, Lorena O.; Esmerino, Erick A.; Pollonio, Marise A.R.; Cruz, Adriano G.
Abstract: The conceptual representation and sensory profiling of low sodium salted meat containing different flavor enhancers (n = 9) were investigated using the Q methodology. Seventy consumers performed a Q-sorting task having in mind the health concept, using a hedonic test and sensory description of the samples. Regular sodium salted meats were associated to the health concept and were characterized by as too much salt, fatty, salty taste, strange taste, and high blood pressure, while the low-sodium samples were associated with good appearance, metallic taste, and healthy. The Health questionnaire showed it is a valorization of food with improved sensory characteristics in addition and the importance of physical and emotional health. Our findings suggested the Q methodology can be an interesting tool for meat processors, together with the traditional sensory test with consumers, to obtain more consistent and complementary information about meat products. Highlights: Q methodology applied to salted meat with partial substitution of NaCl by blends of KCl Adequate conceptual mapping regards the technological aspects Consistent sensory profiling and drivers of liking Low sodium meat products are associated to health concept.